2006
DOI: 10.1021/cm052774q
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Luminescence of Lu2O3:Eu Ceramics upon Excitation with Synchrotron Radiation in the Vicinity of Band Gap Energy

Abstract: Synchrotron radiation has been used to characterize the low-temperature (10 K) spectroscopic properties of Lu 2 O 3 :Eu phosphors containing varying amount of the dopant. Upon excitation at energies in the vicinity of the band gap, the nominally undoped specimen produced three different emissions. The highest energy luminescence, located at 260 nm, was attributed to direct recombination of electrons and holes. We also found a broad band emission at 380 nm, which we attribute to self-trapped excitons (STEs) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 18 publications
3
37
0
Order By: Relevance
“…In the 950-1050 nm spectral region we can see a set of transitions related to the 2 F 5/2 → 2 F 7/2 emission of Yb 3+ . In the excitation spectra we can observed two bands, a broader and stronger one centered at 225 nm, assigned to the 2 F 7/2 → CT transition and less intense, sharp band at 212 nm that can be related to the formation of a free exciton [18,19]. All the emission lines can be excited both at 212 and 225 nm.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the 950-1050 nm spectral region we can see a set of transitions related to the 2 F 5/2 → 2 F 7/2 emission of Yb 3+ . In the excitation spectra we can observed two bands, a broader and stronger one centered at 225 nm, assigned to the 2 F 7/2 → CT transition and less intense, sharp band at 212 nm that can be related to the formation of a free exciton [18,19]. All the emission lines can be excited both at 212 and 225 nm.…”
Section: Resultsmentioning
confidence: 96%
“…For the latter system the Scheme 1. The higher energetic band has an inflection on its lower energetic edge centered at 377 nm that can be recognized as the host lattice emission [18,19]. The energy separation between the two emission bands is 8570 cm −1 , less then energy difference between 2 F 7/2 and 2 F 5/2 states of Yb 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…Lu 2 O 3 -ceramic powders with a molar ratio Lu : Si = 8 : 1 represent systems with efficient energy transfer from the ceramic matrix to the Eu 3+ ions resulting from a recombination of excited electrons to the conduction band and holes left in the valence band. 30) Taking these factors into consideration, it can be observed a good consistency between 20) indicating that both systems are quite comparable; also it is observed that increasing the SiO 2 content at a Lu : Si = 8 : 1 molar ratio, the intensity of the luminescence is enhanced effect that can be observed both powders and films.…”
Section: Photoluminescence Propertiesmentioning
confidence: 84%
“…Just below 220 nm we observe a band, whose position and shape change with temperature. In the past it was showed that fundamental absorption of the lutetia host lattice is located just in this range of wavelengths [13]. At least up to 100 K the band contains the very characteristic sharp narrow structure of free exciton (FE) absorption peaking around 213.3-213.5 nm.…”
Section: Resultsmentioning
confidence: 99%